Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

A concise chemoenzymatic total synthesis of neutral Globo-series glycosphingolipids Globo A and Globo B, and Forssman and para-Forssman antigens - Yu-Ching Chiang; Chun-Yen Wu; Pei-Yun Chiang; Avijit K. Adak; Chun-Cheng Lin (Glycoconjugate Journal, 2023)

Exposure to incense burning, biomarkers, and the physical health of temple workers in Taiwan - Su-Er Guo; Pamela A. Ratner; Sung-Chih Tseng; Chieh-Mo Lin; Miao-Ching Chi; Chiang-Wen Lee; Ying-Chun Yu (Environmental Science and Pollution Research, 2023)
Incense burning releases heavy particulate matter (PM) and nitrogen dioxide (NO 2 ), known to have adverse effects on human health. Long-term exposure to PM and NO 2 increases inflammatory cytokine levels and can induce respiratory diseases. This study examined the association between incense burning exposure and the health status, especially inflammatory biomarkers, of temple workers and volunteers in Taiwan. The longitudinal observational study compared adult temple workers and volunteers, with long-term incense burning exposure, to residents from outpatient clinics in the Chiayi area. Forced expiratory volume in 1 s (FEV1) and serum and exhaled breath condensate (EBC) cytokines were assessed. Nonparametric Mann-Whitney U tests were used to compare cytokine levels of the exposure and control groups during the cold and hot weather seasons. FEV1 was significantly more diminished in the exposed group than in the control group during the cold season. Exposure status was associated with greater hot-cold seasonal differences in serum interleukins (IL)-1β (regression coefficient ( B ) = 6.6, 95% confidence interval (CI) = 5.0 to 8.3, p < .001), IL17-A ( B = 2.4, 95% CI = 0.3 to 4.5, p = .03), and plasminogen activator inhibitor [PAI]-1 ( B = 5.4, 95% CI = 1.5 to 9.3, p = .009). After adjusting for confounders, the groups’ serum levels of IL-1β, IL-17A, and PAI-1 significantly differed. EBC cytokines did not show significant differences. Elevated levels of IL-1β, IL17-A, and PAI-1 have been associated with various autoinflammatory syndromes and diseases. Given the cultural significance of incense burning, culturally sensitive interventions, including education, policy development, and program implementation, are crucial to protect individuals’ health, especially temple workers, from the adverse effects of exposure, addressing the manufacture, importation, and sale of incense.

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Clay nanosheets simultaneously intercalated and stabilized by PEGylated chitosan as drug delivery vehicles for cancer chemotherapy - Hsuan-Jung Huang; Shih-Yu Huang; Tzu-Hao Wang; Tzu-Yun Lin; Nan-Ching Huang; Orion Shih; U-Ser Jeng; Che-Yi Chu; Wen-Hsuan Chiang (Carbohydrate Polymers, 2023)

Dynamic Co-Simulation Analysis and Control of an IEA 15 MW Offshore Floating Semi-Submersible Wind Turbine under Taiwan Offshore-Wind-Farm Conditions of Wind and Wave - Cherng-Jer Chueh; Chun-Hung Chien; Ching Lin; Ting-Yan Lin; Mao-Hsiung Chiang (Journal of Marine Science and Engineering, 2023)
This study aims to develop dynamic co-simulation and control for analyzing the IEA 15 MW semi-submersible floating wind turbine under Taiwan offshore-wind-farm conditions of wind and wave. The IEA 15 MW wind turbine is mounted on a UMaine VolturnUS-S reference platform with a mooring system designed for a water depth of 70 m, in this study. The dynamic co-simulation combines software of SIMPACK, MATLAB/SIMULINK, AeroDyn, HydroDyn, WAMIT, and MAP++ to achieve the complex dynamic simulation of aerodynamics, hydrodynamics, mechanism dynamics and control system dynamics. In addition, this study proposes a novel power-control strategy combining fuzzy sliding-mode control with additional pitching-rate feedback. Since the motion of the floating platform, especially the pitching motion, contributes to power oscillation, the proposed novel power-control strategy with additional pitching-rate feedback can reduce the influence of the floating-platform oscillation motion, and is verified under different conditions.

The Spatial Variation in Chlorophyte Community Composition From Coastal to Offshore Waters in a Subtropical Continental Shelf System - Yun-Chi Lin; Chien-Pang Chin; Wei-Ting Chen; Ching-Ting Huang; Gwo-Ching Gong; Kuo-Ping Chiang; Xin-Bei Chen (Frontiers in Marine Science, 2022)
Globally, the continental shelf occupies less than 10% of the total sea surface, but supports substantial primary production and fisheries. Photosynthetic picoeukaryotes (PPE) are important primary producers in marine ecosystems, and chlorophytes make a significant contribution to PPE abundance. Although the distribution of chlorophytes has been widely studied, little is known about how their community composition varies along the coastal-offshore gradient in subtropical continental shelf waters. To better understand their spatial variations, we employed metabarcoding data of 18S rRNA V4 gene to examine chlorophyte composition within the surface and deep chlorophyll maximum (DCM) layers over the continental shelf in the East China Sea (ECS) with high-resolution sampling. Our results indicate a higher chlorophyte diversity in the surface layer than in the DCM. In addition, we found that chlorophytes in oligotrophic Kuroshio surface water were the most diverse, with a higher percentage of Chloropicophyceae, prasinophyte clade V, prasinophyte clade IX, Palmophyllophyceae and Chlorodendrophyceae. In more eutrophic waters along the coast and within the DCM layer, chlorophytes were dominated by Mamiellophyceae. A significant spatial variation in community composition occurred along the nutrient gradient in the subtropical continental shelf ecosystem, varying from Mamiellophyceae-dominant in coastal water to Chloropicophyceae-dominant in offshore water. Furthermore, at a low saline coastal station, which had the lowest chlorophyte diversity, Picochlorum (Trebouxiophyceae) was dominant. Overall, chlorophyte diversity was positively correlated with temperature, and negatively correlated with silicate concentration. This study revealed that terrestrial input into continental systems influences chlorophyte diversity in the subtropical northwestern Pacific Ocean.

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Movement behaviour of released wild and farm-raised dolphinfish Coryphaena hippurus tracked by pop-up satellite archival tags - Shian-Jhong Lin; Michael K. Musyl; Sheng-Ping Wang; Nan-Jay Su; Wei-Chuan Chiang; Ching-Ping Lu; Kazuki Tone; Chang-Ying Wu; Akira Sasaki; Itsumi Nakamura; Kazuyoshi Komeyama; Ryo Kawabe (Fisheries Science, 2019)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Changes in Trace Elements During Early Stages of Chronic Kidney Disease in Type 2 Diabetic Patients - Ching-Chiang Lin; Ching-Tang Shih; Chien-Hung Lee; Yeou-Lih Huang (Biological Trace Element Research, 2018)

The Divalent Elements Changes in Early Stages of Chronic Kidney Disease - Wan-Ju Kung; Ching-Tang Shih; Chien-Hung Lee; Ching-Chiang Lin (Biological Trace Element Research, 2018)

Seasonal variation and source apportionment of PM2.5-bound trace elements at a coastal area in southwestern Taiwan - Su-Lun Hwang; Miao-Ching Chi; Su-Er Guo; Yu-Ching Lin; Chiang-Ting Chou; Chieh-Mo Lin (Environmental Science and Pollution Research, 2018)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

The summer distribution of coccolithophores and its relationship to water masses in the East China Sea - Lee-Kuo Kang; Hsing-Ming Lu; Pei-Ting Sung; Ya-Fan Chan; Yun-Chi Lin; Gwo-Ching Gong; Kuo-Ping Chiang (Journal of Oceanography, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Production of cyclodextrin glucanotransferase from an alkalophilic Bacillus sp. by pH-stat fed-batch fermentation - Chou-Chiang Kuo; Ching-An Lin; Jing-Yi Chen; Ming-Tse Lin; Kow-Jen Duan (Biotechnology Letters, 2009)

Genetic analysis of an attenuated Papaya ringspot virus strain applied for cross-protection - Chu-Hui Chiang; Chun-Yee Lee; Ching-Hsien Wang; Fuh-Jyh Jan; Shih-Shun Lin; Tsung-Chi Chen; Joseph A. J. Raja; Shyi-Dong Yeh (European Journal of Plant Pathology, 2007)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Isolation and characterization of microsatellite loci in Acrossocheilus paradoxus (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Kui-Ching Hsu; Jiang-Ping Wang; Xiang-Lin Chen; Tzen-Yuh Chiang (Conservation Genetics, 2004)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)